# (3x)(4x)=12x

## Simple and best practice solution for (3x)(4x)=12x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (3x)(4x)=12x equation:

Simplifying
(3x)(4x) = 12x
Remove parenthesis around (3x)
3x(4x) = 12x
Remove parenthesis around (4x)
3x * 4x = 12x
Reorder the terms for easier multiplication:
3 * 4x * x = 12x
Multiply 3 * 4
12x * x = 12x
Multiply x * x
12x2 = 12x
Solving
12x2 = 12x
Solving for variable 'x'.
Reorder the terms:
-12x + 12x2 = 12x + -12x
Combine like terms: 12x + -12x = 0
-12x + 12x2 = 0
Factor out the Greatest Common Factor (GCF), '12x'.
12x(-1 + x) = 0
Ignore the factor 12.
Subproblem 1Set the factor 'x' equal to zero and attempt to solve:
Simplifying
x = 0
Solving
x = 0
Move all terms containing x to the left, all other terms to the right.
Simplifying
x = 0
Subproblem 2Set the factor '(-1 + x)' equal to zero and attempt to solve:
Simplifying
-1 + x = 0
Solving
-1 + x = 0
Move all terms containing x to the left, all other terms to the right.
Add '1' to each side of the equation.
-1 + 1 + x = 0 + 1
Combine like terms: -1 + 1 = 0
0 + x = 0 + 1
x = 0 + 1
Combine like terms: 0 + 1 = 1
x = 1
Simplifying
x = 1Solutionx = {0, 1}`